2014
DOI: 10.1159/000363748
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Misoprostol versus a Rectal Nonsteroidal Anti-Inflammatory Drug to Reduce Pain during Pipelle Endometrial Biopsies: A Prospective, Randomized, Placebo-Controlled Trial

Abstract: Background: To evaluate and compare the efficacy of vaginal misoprostol and a rectal nonsteroidal anti-inflammatory drug (NSAID) on pain relief during Pipelle endometrial biopsies in a placebo-controlled randomized study. Methods: One hundred and fifty-one women who had an indication for a Pipelle endometrial biopsy were randomized into three groups as follows: group 1, vaginal misoprostol; group 2, rectal NSAID, and group 3, control. After the procedure, the women were asked to record their pain severity on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Although several studies concluded that Pipelle significantly produced less pain than D&C [10,11,12], other studies reported the occurrence of mild-to-severe pain during Pippelle endometrial sampling [13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies concluded that Pipelle significantly produced less pain than D&C [10,11,12], other studies reported the occurrence of mild-to-severe pain during Pippelle endometrial sampling [13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…The secondary outcome of the study was patient acceptability, vasovagal symptoms and analgesic requirements. The study did not demonstrate a reduction in pain during Pipelle endometrial biopsies for patients receiving either vaginal misoprostol or rectal indomethacin when compared to patients receiving placebo treatment [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Four hundred micrograms of oral or vaginal misoprostol is found useful for cervical dilatation up to 10 mm prior to operative hysteroscopy [15]. Other studies have denied any benefits from oral use of 400 µg of misoprostol before hysteroscopy or even before pipelle sampling of the endometrium [16,17]. The majority of these studies compared misoprostol to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of route of administration, no benefit was demonstrated, and there is possible harm given that misoprostol itself causes cramping. 31,32 Several trials demonstrated a modest benefit on pain with an intrauterine lidocaine infusion when compared with saline. 33,34 This is most commonly administered transcervically with a 91 Pain Management for Gynecologic Procedures • CME Review Article syringe attached to an angiocatheter, which is left in place between 3 and 5 minutes prior to endometrial biopsy to prevent backflow out of the cervical os.…”
Section: Endometrial Biopsymentioning
confidence: 99%